Faktor-Faktor yang Berhubungan dengan Stres Kerja Pada Petugas Pemadam Kebakaran Kompi C di Kota Padang - Permatasari, Putri; Hendra, H (Universitas Aisyah Pringsewu, 2018)
Stress is actually a form of response to a person, both physically and mentally, to a change in the environment that felt annoying and cause self in danger. One of the professions that have a very high risk of exposure to stress is a firefighters. This study was conducted in Fire department South Padang in May-June 2016. Study sample as many as 116 respondents. In this study, analysis performed descriptive analyzes to look at the picture of the frequency distribution of each variable both dependent and independent variables, including: work stress, workload, a routine work, work environment, interpersonal relations with a boss, interpersonal relations with colleagues, promotion (the increase in the level of office), salary, a role in the organization, family problems, economic issues and type of personality. While the bivariate analysis aims to see whether the relationship between the independent variables and the dependent variable and observed differences in the frequency value. Based on the results study, firefighters who experienced job stress as much as 29,3 percent. While the variables that have an association with job stress events such as workload (p value 0,020), a routine work (p value 0,033), and promotion (the increase in the level of office) (p value 0,024). There are some suggestions that can of work stress in firefighters by held a relaxation activities and conduct spiritual cleansing.